P-Type Nitrogen-Doped ZnO Films Prepared by In-Situ Thermal Oxidation of Zn3N2 Films*Supported by the National Natural Science Foundation of China under Grant Nos 10775033 and 11075038. (May 2016) - Jin 靳, Yu-Ping 玉平; Zhang 张, Bin 斌; Wang 王, Jian-Zhong 建中; Shi 施, Li-Qun 立群
Abstract : P-type nitrogen-doped ZnO films are prepared successfully by in-situ thermal oxidation of Zn3 N2 films. The prepared films are characterized by x-ray diffraction, non-Rutherford backscattering (non-RBS) spectroscopy, x-ray photoelectron spectroscopy, and photoluminescence spectrum. The results show that the Zn3 N2 films start to transform to ZnO at 400°C and the total nitrogen content decreases with the increasing annealing temperature. The p-type films are achieved at 500°C with a low resistivity of 6.33Ω·cm and a high hole concentration of +8.82 × 10 17 cm −3, as well as a low level of carbon contamination, indicating that the substitutional nitrogen (NO ) is an effective acceptor in the ZnO:N film. The photoluminescence spectra show clear UV emissions and also indicate the presence of oxygen vacancy (VO ) defects in the ZnO:N films. The p-type doping mechanism is briefly discussed.